Light at the museum – A near impossible result. Issue 5 (September 2020) - Power, AC; Ingleby, S; Chapman, J; Cozzolino, D
The monitoring and quantification of the illegal harvest of protected animal products is very vital for the conservation and protection of endangered species. Most of the methods and techniques used in the trade of these products are recognised to be incredibly time consuming and labour intensive requiring significant analyst expertise. In this study, we have demonstrated the potential of near-infrared spectroscopy combined with either principal component analysis or partial least square discriminant analysis regression as a rapid and non-invasive tool to classify horn and ivory samples stored in the Australian Museum, Sydney. This study has also demonstrated the attractiveness of the near-infrared technique as a screening tool that could revolutionise the tracking and identification of contraband materials produced from horn and ivory biomaterials.